Alternating therapy with osimertinib and afatinib for treatment-naive patients with EGFR-mutated advanced non-small cell lung cancer: A single-group, open-label phase 2 trial (WJOG10818L). (June 2022) - Hayashi, Hidetoshi; Yonesaka, Kimio; Nakamura, Atsushi; Fujimoto, Daichi; Azuma, Koichi; Sakata, Shinya; Tachihara, Motoko; Ikeda, Satoshi; Yokoyama, Toshihide; Hataji, Osamu; Yano, Yukihiro; Hirano, Katsuya; et al.
Highlights: Alternation of osimertinib and afatinib was evaluated for patients with metastatic treatment-naïve EGFR-mutated NSCLC in this phase 2 trial. Although the 12-month PFS probability was 70.2%, which did not meet the primary end point, the median PFS was 21.3 months suggesting the promising efficacy of this alternative therapy. Our results are indicative of the feasibility of alternating therapy with osimertinib and afatinib. The study treatment is effective even in patients with TP53 mutations or EGFR compound mutations from exploratory cfDNA analysis results. Abstract: Introduction: Alternation of osimertinib and afatinib is a potential approach to overcome osimertinib resistance and to allow complementation of drug efficacy without compromising safety in patients with epidermal growth factor receptor gene ( EGFR )–mutated non–small cell lung cancer (NSCLC). Methods: Treatment-naive patients with stage IV NSCLC harboring an activating EGFR mutation (L858R or exon-19 deletion) were enrolled. Alternating cycles of osimertinib at 80 mg/day for 8 weeks followed by afatinib at 20 mg/day for 8 weeks were administered. The primary end point was 12-month progression-free survival (PFS) probability. Results: Forty-six patients were enrolled and treated with study therapy. The 12-month PFS probability was 70.2% (60% confidence interval [CI], 63.9–75.6%; 95% CI, 54.2–81.5%), which did not meet the primary end point. After a median follow-up time of 25.7 months, the median PFS was 21.3 months (95% CI, 16.3 months–not reached). The overall response rate was 69.6% (95% CI, 54.2–82.3%). The most common treatment-related adverse events (any grade or grade ≥ 3, respectively) were diarrhea (73.9%, 4.3%), rash acneiform (63.0%, 2.2%), and paronychia (52.2%, 0%). Five cases of pneumonitis, two of grade 2 and thres of grade 3, were apparent, all of which developed during osimertinib treatment. Exploratory evaluation of circulating tumor DNA suggested that coexisting TP53 mutations did not influence PFS for the alternating therapy. Conclusions: Alternating therapy with osimertinib and afatinib for treatment-naive patients with EGFR- mutated advanced NSCLC did not meet its primary end point, despite the encouraging efficacy and safety profile of this treatment strategy.